Poems and prayers to nature's sublime inspiration - Bailey, Scott J., author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member; Twarogowski, Leroy A., committee member; Sullivan, Patrice M., committee member (Colorado State University. Libraries, 1997)
In the intimate folds of nature, I have found places which have inspired me to revel in them, to remember them, and to research with paint the visual and emotional power they hold. They are microcosms of life's universal rhythms which sing praise to the sublime wisdom of the macrocosm. My journey through them affirms personal growth, understanding, and renewal; the evidence of these things lies in the sensitively crafted and painted handmade objects which are left behind. I have made myself a conduit through which nature informs art. With my process of laying down a primal and gestural web of marks and later weaving paint over and through them, expression is crystallized and then built upon through memory re-construction and aesthetic choices. Sanding, scraping, wiping, and veiling of paint make reference to the ethereal forces of nature while creating visceral surfaces on the art objects. In this body of work, traditions are simultaneously being championed and challenged. The tradition of using flat, rectangular planes to allude to space is embraced, while the angular juxtaposition of the panels against each other calls the rules of two-dimensional painting into question. They are paintings, yet as screens they have utility and function. The screens borrow from the intelligence of the Japanese master screen painters, but stretch the limits of the prescribed formats beyond the legacy. These are the most recent footsteps of my journey, inspired by real, visual experiences of nature and colored by perspective, time, and the very acts of remembering and painting.
Keywords: Screen painting; Painting, American -- 20th century